Behavioral Neuroscience of Drug Addiction - Self, David W.; Staley Gottschalk, Julie K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume highlights current state-of-the-art approaches and important findings on the behavioral neurobiology of drug addiction by prominent neuroscientists. Preclinical chapters span synaptic neuroplasticity associated with drug use, the neural systems underlying conditioned drug effects implicated in drug craving, and the role of sensitization and withdrawal processes in addictive behavior. Chapters on human studies emphasize neuroimaging of neurotransmitters and receptors, drug craving and other cognitive abnormalities in human drug abusers. Human studies also describe work on genetic vulnerability and the neuroeconomics of drug addiction, and novel pharmacological approaches to drug abuse treatment.
Neuroplastic Alterations in the Limbic System Following Cocaine or Alcohol Exposure -- Dopamine Signaling in the Nucleus Accumbens of Animals Self-Administering Drugs of Abuse -- Amygdala Mechanisms of Pavlovian Psychostimulant Conditioning and Relapse -- Prefrontal Cortical Regulation of Drug Seeking in Animal Models of Drug Relapse -- Neural Substrates of Psychostimulant Withdrawal-Induced Anhedonia -- Sensitization Processes in Drug Addiction -- Imaging Receptor Changes in Human Drug Abusers -- Imaging Neurotransmitter Release by Drugs of Abuse -- Imaging Cognitive Deficits in Drug Abuse -- Neural Markers of Genetic Vulnerability to Drug Addiction -- The Role of Executive Control in Human Drug Addiction -- The Behavioral Economics of Drug Dependence: Towards the Consilience of Economics and Behavioral Neuroscience -- Novel Pharmacological Approaches to Drug Abuse Treatment.
Keywords: Medicine; Neurosciences; Neurochemistry; Toxicology; Radiology, Medical; Psychiatry; Psychopharmacology; Biomedicine; Neurosciences; Neurochemistry; Pharmacology/Toxicology.; Psychiatry; Psychopharmacology; Imaging / Radiology